The electroremediation of wastewater with Orange II, colloidal motor oil, and synthetic domestic sewerage as waste models via treatment with Iron(VI) - ROBERT DE ANGELO, BOLINAS (Archīum Ateneo, 2016)
Iron(VI) as FeO42- more commonly known as ferrate, is a green alternative being developed for wastewater treatment. This study synthesized sodium ferrate (Na2FeO4) to treat three synthetic wastewater models containing Orange II (an azo-dye), colloidal mot